Direito fundamental à razoável duração do processo e sustentabilidade social: análise sobre demandas por prestação jurisdicional de saúde no estado da Paraíba - Barbosa, João Batista (2019)
With the advent of Constitutional Amendment nº. 45/2004 was included in 5th article of the Federal Constitution of 1988, item LXXVIII, which contains the right to a reasonable duration of proceedings. After approximately thirteen years, the ombudsman's offices still receive many complaints regarding judicial delays. It turns out that the constitution referred to recognized several social values such as the right to health. Violated these rights, the possibility of judicialization opens. However, if there is a disproportionate delay in settling the dispute, the decision may no longer be of practical use. In this sense, this dissertation has as its object the study of the right to a reasonable duration of the proceedings and the quantitative analysis of claims for health care in the State of Paraíba. Therefore, statistical data on original resources and actions will be analyzed and compared; international declarations and conventions examined; the homeland legislation and study of the related doctrine with the subject. Finally, is evaluated how social sustainability is affected by the decisions of the Court of Justice of the State of Paraíba, and proposes a way to contribute to the realization of the right to health.